1975
DOI: 10.1099/00222615-8-1-77
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cryptococcus Neoformans by Pseudomonas Aeruginosa

Abstract: PLATES IV AND VD URING an investigation of Cryptococcus neoformans isolated from clinical specimens, we observed that growth of the fungus was considerably reduced in the vicinity of colonies of Pseudomonas aeruginosa. This phenomenon was first noted by Fisher (1954), who found that the inhibitory effect was exhibited only by living cultures of certain strains of P. aeruginosa. His efforts to isolate the inhibitor were unsuccessful and no further report on this phenomenon has since appeared. We report here a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Twenty years later, Teoh-Chan et al reported an initial attempt to isolate and characterize the inhibitory substances involved in 1974 [13]. However, the literature about the inhibitory effect of Pa on C. neoformans is equivocal [12, 13]. In this study, we revealed the mechanism used by Pa to inhibit the growth of Cryptococcus spp.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Twenty years later, Teoh-Chan et al reported an initial attempt to isolate and characterize the inhibitory substances involved in 1974 [13]. However, the literature about the inhibitory effect of Pa on C. neoformans is equivocal [12, 13]. In this study, we revealed the mechanism used by Pa to inhibit the growth of Cryptococcus spp.…”
Section: Introductionmentioning
confidence: 70%
“…Previous reports reveal that Pa inhibits the growth of different microbes [1013]. However, the mechanism that underlines the inhibitory effects of Pa on Cryptococcus species has not been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While only a few studies concerning this biological phenomenon have been done in vitro, the results suggest that interaction between Pseudomonas aeruginosa and Candida albicans could be important for an accurate laboratory diagnosis of mixed bacterial/fungal infections. Furthermore, some reports of co-isolations of micro-organisms in clinical specimens have shown an inhibitory effect of Pseudomonas aeruginosa on Candida albicans [9,10], Cryptococcus neqformans [11,12], Histoplasma capsulatum, Blastomyces dermatitidis [ 13 ], Aspergillus fomigatus [14] and Trichophyton rubrum [15]. It was thus important to investigate whether P. aeruginosa can inhibit the growth of the major yeast bloodstream pathogens in a blood culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…Hughes and Kim (7) demonstrated that in CF patients infected with PA, only 10% of patients produced positive CA skin tests compared with 30% positivity in those free of PA, indicating that the antifungal substance produced by PA prevents Candida infections. There are also studies investigating the growth inhibition effect of PA in Cryptococcus species (12,13). However, to the best of our knowledge, there have been no studies regarding the isolation of Cryptococcus species from patients with CF.…”
Section: Discussionmentioning
confidence: 99%